Konservasi Burung di Hutan Adat: Refleksi Kritis Mahasiswa Belajar dari Kearifan Lokal Desa Demulih Bangli - Sang Putu Kaler Surata; I Gusti Agung Sri Rwa Jayantini; Ida Ayu Made Sri Widiastuti; I Gusti Agung Paramitha Eka Putri (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
This paper focuses on undergraduate students’ critical reflection in a service-learning (S-L) project to promote the conservation of the birds based on local wisdom in a village in Bali. The students are working in a partnership with researchers and local communities from a traditional rural village, namely Desa Adat Demulih, Bangli regency. The objective of this paper is to show what students can learn and how they gain personal growth, civic-learning and academic enhancement during the S-L project. The finding shows students’ positive improvements in self-confidence, civic awareness, and community engagement. This study indicates a significance role of S-L based on critical reflection in documenting, deepening and promoting local identity and culture as a key component of community-bird conservation. In line with the finding, this study is expected to show how the interdisciplinary studies are cooperatively applied to draw knowledge from different disciplines by acquiring mutual relationship in learning their local knowledge.